Effect of laser phototherapy in the prevention and treatment of chemo-induced mucositis in hamsters - Talita Christine Camilo Lopez; Manoela Domingues Martins; Vanessa Christina Santos Pavesi; Leila Soares Ferreira; Sandra Kalil Bussadori; Maria Stella Moreira; Marcia Martins Marques (Brazilian Oral Research, 2013)
The aim of this study was to investigate the effect of laser phototherapy (LPT) in the prevention and/or treatment of oral mucositis induced by 5-fluorouracil (5-FU; Eurofarma, São Paulo, Brazil) in hamsters. Ninety-six hamsters were divided into four groups (n = 24): Control (no treatment); Preventive [LPT from day (D) D-5 to D+5]; Therapeutic (LPT from D+5 to D+15); and Combined (preventive plus therapeutic LPT from D-5 to D+15). The animals received an intraperitoneal injection of 5-FU on Days 0 and 2. The pouch mucosa was scratched on Days 3 and 4. The irradiation parameters were: indium-gallium-aluminum-phosphide (InGaAlP) diode laser (MM Optics, São Carlos, Brazil) (660 nm), beam area of 0.036 cm2, 40 mW, 1.11 W/cm2, 6.6 J/cm2, power density applied daily of 39.6 J/cm2, in punctual mode (six points and six seconds per point) and contact mode, one application per day. The animals were sacrificed on Days 0, 5, 10 and 15 (n = 6) and weighed, and the pouch mucosa was removed for histopathological analysis. Clinical and corresponding histological scores were compared using ANOVA and Tukey's test (p ≤0.05). Similar weight losses ranging from 5% to 10% occurred in all groups. The therapeutic group had significantly lower clinical and histological scores than the other groups at Day 10. This study showed that positive effects on oral mucositis management were obtained only when LPT was applied in the therapeutic protocol (from D+5 to D+15 after chemotherapy).